2012
DOI: 10.1038/bjc.2012.480
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor phosphorylation at serine 515 by Cdk1 predicts biochemical relapse in prostate cancer patients

Abstract: Background:Prostate cancer cell growth is dependent upon androgen receptor (AR) activation, which is regulated by specific kinases. The aim of the current study is to establish if AR phosphorylation by Cdk1 or ERK1/2 is of prognostic significance.Methods:Scansite 2.0 was utilised to predict which AR sites are phosphorylated by Cdk1 and ERK1/2. Immunohistochemistry for these sites was then performed on 90 hormone-naive prostate cancer specimens. The interaction between Cdk1/ERK1/2 and AR phosphorylation was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…In addition, the level of pAR S515 was related with EGF-induced PCa cell growth 41. pAR S515 was also proved to be a potential predictive marker for relapse in PCa 42. These studies indicated that pAR S515 is related to PCa progression.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the level of pAR S515 was related with EGF-induced PCa cell growth 41. pAR S515 was also proved to be a potential predictive marker for relapse in PCa 42. These studies indicated that pAR S515 is related to PCa progression.…”
Section: Discussionmentioning
confidence: 89%
“…It is interesting to note that no enrichment of ensemble peaks at EZH2-repressed genes was observed. Among these EZH2-activated genes, several have been indicated to play critical roles in cancer progression, such as ATAD2 (23), CDK1 (24) and FOXM1 (25). In prostate cancer patient samples (26), these signature genes are significantly upregulated in the metastatic prostate tumors comparing to the primary cancer samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…95). There are many examples of serine/threonine and tyrosine kinases implicated in AR phosphorylation and amongst the most interesting are Aurora kinase A (Aurora-A), 96 cyclin-dependent kinase 1 (Cdk1), 97,98 PIM1 kinase, 99 Src and Ack1; 100102 all of these are targets of small molecule inhibitors in clinical development.…”
Section: Mechanisms Of Maintained Ar Activity In Crpcmentioning
confidence: 99%